Alien and native plant establishment in grassland communities is more strongly affected by disturbance than above‐ and below‐ground enemies. (September 2016) - Müller, Gregor; Horstmeyer, Lena; Rönneburg, Tilman; van Kleunen, Mark; Dawson, Wayne
Summary: Understanding the factors that drive commonness and rarity of plant species and whether these factors differ for alien and native species are key questions in ecology. If a species is to become common in a community, incoming propagules must first be able to establish. The latter could be determined by competition with resident plants, the impacts of herbivores and soil biota, or a combination of these factors. We aimed to tease apart the roles that these factors play in determining establishment success in grassland communities of 10 alien and 10 native plant species that are either common or rare in Germany, and from four families. In a two‐year multisite field experiment, we assessed the establishment success of seeds and seedlings separately, under all factorial combinations of low vs. high disturbance (mowing vs mowing and tilling of the upper soil layer), suppression or not of pathogens (biocide application) and, for seedlings only, reduction or not of herbivores (net‐cages). Native species showed greater establishment success than alien species across all treatments, regardless of their commonness. Moreover, establishment success of all species was positively affected by disturbance. Aliens showed lower establishment success in undisturbed sites with biocide application. Release of the undisturbed resident community from pathogens by biocide application might explain this lower establishment success of aliens. These findings were consistent for establishment from either seeds or seedlings, although less significantly so for seedlings, suggesting a more important role of pathogens in very early stages of establishment after germination. Herbivore exclusion did play a limited role in seedling establishment success. Synthesis : In conclusion, we found that less disturbed grassland communities exhibited strong biotic resistance to establishment success of species, whether alien or native. However, we also found evidence that alien species may benefit weakly from soilborne enemy release, but that this advantage over native species is lost when the latter are also released by biocide application. Thus, disturbance was the major driver for plant species establishment success and effects of pathogens on alien plant establishment may only play a minor role. Abstract : In conclusion, we found that less disturbed grassland communities exhibited strong biotic resistance to establishment success of species, whether alien or native. However, we also found evidence that alien species may benefit weakly from soilborne enemy release, but that this advantage over native species is lost when the latter are also released by biocide application. Thus, disturbance was the major driver for plant species establishment success and effects of pathogens on alien plant establishment may only play a minor role.